Dragon fruits as an alternative source of colorants: evaluation of antibacterial activity and colouring capacity - Roriz, Custódio Lobo (2019)
Betalains are a group of secondary metabolites named chromoalkaloids that are synthesized from tyrosine. These compounds have gained some attention in the last few years mainly due to their interesting bioactive potential, namely antioxidant, antimicrobial, and other bioactive properties [1]. Their strong and vibrant colours are also one of the characteristics by which these compounds have gained visibility in the food and pharmaceutical industries [2]. Betalains can be divided in two groups regarding the colour range: betaxanthins in the orange to yellow range, and betacyanins in the purple to pink range. Thereby, these compounds can be used as natural colouring agents, providing alternatives to the massively used artificial counterparts [3]. Although there are already some natural options in the market, these are not enough to meet the needs of the food industry, due to the growing concern of consumers regarding what they eat. Thus, the objectives of this work were to: i) obtain bioactive extracts and with strong colouring capacity from the epicarp of two pitaya varieties, white-fleshed pitaya Hylocereus undatus (Haworth) Britton & Rose (WFP) and red-fleshed pitaya Hylocereus costaricensis (F.A.C.Weber) Britton & Rose (RFP); ii) chemically characterize the betalains’ content through HPLC-DAD-ESI/MS; iii) evaluate the bioactive properties of the extracts, namely antimicrobial activity. The extracts were obtained through a dynamic maceration assisted by heat, and the betacyanins’ profile was characterized by HPLC-DAD-ESI/MS. The antibacterial capacity was determined against a panel of Gram-negative and Gram-positive bacteria using the colorimetric method of rapid detection with p-iodonitrotetrazolium chloride (INT), and the responses obtained were expressed as minimum inhibitory (MIC) and minimum bactericidal (MBC) concentrations. By the chromatographic analysis of the extracts it was possible to identify six compounds in both samples. For the WFP the major compounds identified were 6'-O-malonylbetanin (phylocactin), followed by 4'-malonyl-betanin, while for the RFP the major compound found was phylocactin. In the evaluation of the antibacterial activity, both extracts showed MIC and MBC values that ranged from 10 to 20 mg/mL. Gram-positive bacteria showed to be more susceptible to both extracts then the negative strains. Further studies need to be conducted to better understand the correlation between the bioactive potential and the betacyanins’ composition. Nevertheless, these natural matrixes proved to be viable alternatives for obtaining colouring extracts with antimicrobial properties.